Reliability of the Shoulder Symptom Modification Procedure and association of within-session and between-session changes with functional outcomes - Adam Meakins; Stephen May; Chris Littlewood (BMJ Open Sport & Exercise Medicine)
Background Despite being a common problem, there is considerable diagnostic uncertainty with regard to shoulder pain. This uncertainty relates to the reliability and validity of current examination tests. The Shoulder Symptom Modification Procedure (SSMP) has been proposed as an alternative to existing approaches.Objective To evaluate interclinician reliability of the SSMP and the association of within-session and between-session changes on clinical outcome at 1 week, and at 1 and 3 months.Design A single-centre reliability study, with prospective follow-up.Methods Twenty-six patients with shoulder pain were recruited. Following an initial SSMP-based examination, a second examination was performed by a second physiotherapist, blinded to the results of the first examination. Clinical outcome data were completed after 1 week, 1 month and 3 months via theNumeric Pain Rating Scale and the Shoulder PainandDisability Index. Reliability was evaluated using kappa and associations were evaluated using Spearman’s r.Results Inter-rater reliability of the SSMP was moderate (κ=0.47). Association of within-session changes ranged from fair to poor in the short term (r=0.24–0.01) to poor in the mid-term (r=−0.03). The association of between-session changes ranged from substantial to moderate in the short term (r=0.74–0.47) but slight in the mid-term (r=0.22).Conclusions Based on this study, we cannot recommend the SSMP as a reliable tool for physical examination of patients with shoulder pain. The importance of within-session and between-session changes remains uncertain.